The PPARγ ligand ciglitazone regulates androgen receptor activation differently in androgen- dependent versus androgen- independent human prostate cancer cells - Moss, Patrice E. (2010)
The androgen receptor (AR) regulates growth and progression of androgen-dependent as well as androgen-independent prostate cancer cells. Peroxisome proliferator activated receptor gamma (PPARγ) agonists have been reported to reduce AR activation in androgen-dependent LNCaP prostate cancer cells. To determine whether PPARγ ligands are equally effective at inhibiting AR activity in androgen-independent prostate cancer, we examined the effect of the PPARγ ligands ciglitazone and rosiglitazone on C4-2 cells, an androgen- independent derivative of the LNCaP cell line. Luciferase-based reporter assays and Western blot analysis demonstrated PPARγ ligand reduced dihydrotestosterone (DHT)-induced increases in AR activity in LNCaP cells. However, in C4-2 cells these compounds increased DHT-induced AR driven luciferase activity. In addition, ciglitazone did not significantly alter DHT-mediated increases in prostate specific antigen (PSA) protein or mRNA levels within C4-2 cells. siRNA based experiments demonstrated that the ciglitazone-induced regulation of AR activity observed in C4-2 cells was dependent on the presence of PPARγ. Furthermore, overexpression of the AR corepressor cyclin D1 inhibited the ability of ciglitazone to induce AR luciferase activity in C4-2 cells. Thus, our data suggest both PPARγ and cyclin D1 levels influence the ability of ciglitazone to differentially regulate AR signaling in androgen-independent C4-2 prostate cancer cells.